CAUTI FINAL REPORT - TOWNSEND,D (Tufts Archival Research Center, 2007)
Draft; Draft of Townsend and Company final report for Californians Against Unfair Tax Increases (CAUTI). Requests feedback. Analyzes election result and indentifies major obstacles facing the tobacco industry in the campaign. Asks what alternative actions should have been looked into more and maybe utilized. Finds the greatest challenge was allies outside of the "tobacco stream."